Bio-etiek sonder grense en menswaardigheid: 'n Gereformeerd-etiese beoordeling - Rheeder, Riaan (Verbum et ecclesia, 2013)
Bioethics without boundaries and human dignity: A Reformed-ethical assessment. The Universal Declaration of Bioethics and Human Rights (UDBH) seeks to guide the world community in ethical principles with regard to medicine, life sciences and related technologies. Human dignity as a principle was requested by the world community and serves as a point of departure in most human rights instruments, as well as in the UDBH. Human dignity serves as a foundation for ethical principles and human rights. In this article, attention was given to the question of whether human dignity could be accepted as part of the Biblical message. Human dignity as a principle and grounding in the UDBH was accepted by most major religions of the world. There exists today a universal consensus that human dignity is an extremely important concept in bioethics. In light of the Reformed tradition, all human beings have dignity, as they had been created in the image of God. Because God is absolute value, humans have derived, but definite value. Human dignity is not just a status, but also a command. All the ethical principles and human rights in the UDBH should be regarded as a way of giving expression to the dignity of man. When the dignity of the humans beings is infringed upon, an undignified image of God is revealed, and serves as a direct insult to God.